Thermal and physical properties of Barrovian metamorphic sequence rocks in the Ailao Shan-Red River shear zone, and implications for crustal channel flow - Ji, L; Liu, F; Palin, R; Wang, F; Sun, Z (American Geophysical Union, 2024)
The collisional history between Greater India and the Eurasian plate has been well constrained by the study of exhumed Barrovian metamorphic sequence (BMS) rocks in the Himalayan Range. However, in the southeastern Tibetan Plateau, the collisional records have been obscured by intense, regional-scale strike-slip overprinting and recrystallization. Here, in BMS rocks from the Ailao Shan–Red River shear zone (ARSZ), we report the first discovery of a >250 km long, high-pressure (high-P) granulite belt (>1.0 GPa), identified by the presence of relict kyanite and associated decompression reaction textures. Petrological phase equilibrium modeling showed that exposed micaschists in the region represent exhumed middle crust (20–25 km, 600–670°C), while the high-P granulite rocks are remnants of thickened lower crust (45–55 km, 800–850°C). This indicates that the northeast edge of the ARSZ experienced an additional ∼25 km of uplift and exhumation compared to the southwest side, facilitated by brittle thrusting/imbrication along the Ailao Shan fault (micaschists) and ductile extrusion along the Red River fault (granulite). Geochronological study shows that the upper portion of the BMS preserves older metamorphic ages (52–34 Ma) than the lower portion (32–29 Ma), which was attributed to spatial variation in cooling rates. Using calculated P–T–t–d paths, we also examined variation in density and seismic wave speeds for BMS in the ARSZ. Our data correlate with fieldwork conducted elsewhere within the Himalayan Range indicating that the kyanite to sillimanite transition zone may serve as a “cap” for the horizontal migration of melt within the lower crust.